1986
DOI: 10.1088/0031-9155/31/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of CO-γ-irradiated and microwave-heated rat tumour and skin measured in vivo between 0.2 and 2.4 GHz

Abstract: The dielectric properties of a rat tumour (rhabdomyosarcoma R1H), skin and muscle were measured in vivo with an open-ended coaxial line and a computer-controlled system based on a network analyser. The permittivity of the tumour R1H and of the normal tissues in anaesthetised rats was determined at frequencies between 0.2 and 2.4 GHz. No significant differences were observed either between rat tumour and muscle or between normal and 15 Gy irradiated rat tumour and skin. However, after a hyperthermia treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 27 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…It is possible to determine the free water content in tissue by extracting the values of dielectric permittivity (ε ) at around 1 GHz. For example, Zywietz and Knöchel (1986) observed changes of ε at 2.4 GHz for rat skin after a hyperthermia treatment, due to changes in the tissue water content. Peyman et al (2001) reported significant decreases in ε at 900 MHz, 1.8 GHz and 2 GHz for rat tissue (including skin) as a function of age, as a result of decreases of the tissue water content.…”
Section: Drying Process Of Human Finger After Soakingmentioning
confidence: 99%
“…It is possible to determine the free water content in tissue by extracting the values of dielectric permittivity (ε ) at around 1 GHz. For example, Zywietz and Knöchel (1986) observed changes of ε at 2.4 GHz for rat skin after a hyperthermia treatment, due to changes in the tissue water content. Peyman et al (2001) reported significant decreases in ε at 900 MHz, 1.8 GHz and 2 GHz for rat tissue (including skin) as a function of age, as a result of decreases of the tissue water content.…”
Section: Drying Process Of Human Finger After Soakingmentioning
confidence: 99%
“…Peloso et al (1984) measured rat tumour in vitro at 1 MHz to 1 GHz and found no significant difference to normal tissue. Others report results in the microwave frequency range where the differences between normal and tumour tissue stem primarily from differences in water content (Schepps and Foster 1980, Zywietz and Knoechel 1986, Burdette et al 1977. There are no known reports on in vivo measurements of electrical conductivity of hepatic tumours at audio and radio frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency dependence of the permittivity of various mammalian tumor tissues has been reported by several investigators. [Fricke and Morse, 1926;Bottomley and Andrew, 1978;Singh et al, 1979;Rogers et al, 1983;Schepps and Foster, 1980;Chaudhary et al, 1984;Zywietz et al, 1986;Smith et al, 1986;Surowiec et al, 19871. However, data at frequencies below 50 MHz are limited. To the best of our knowledge, only three studies have been reported on the dielectric properties of excised tumor tissues at low radiofrequencies [Bottomley and Andrew, 1978;Smith et al, 1986;Surowiec et al, 19873.…”
Section: Introductionmentioning
confidence: 99%